Improvement of extraction processing conditions for antibacterial compounds from Curcuma longa - Ahmad Raus, Raha; Abdul Malek, Nur Farihah; Bastami, Mohd Saufi; Mat Amin, Noriha (IIUM Press, 2011)
Curcuma longa is a rhizomatous herbaceous perennial plant of the ginger family, Zingiberaceae that is known for its antibacterial property. In this study optimization of extraction processing conditions were detemlined to obtain maximum yield of antibacterial compounds from C. longa. Optimization experiments designed by Box-Behnken (Design Expert Software) were carried out with three parameters considered namely agitation, extraction time and temperature. Analysis of results was done statistically using Analysis of Yariance (ANDYA). The regression equation analysis showed that the optimum condition in producing antibacterial compound \vas 40°C of temperature, 24 hour and at 150 rpm agitation speed gave the maximum diameter of zone inhibition (19.17 mm). The analysis showed that the model (p < 0.01) is significant for inhibiting the bacterial activity.